The power of habit : why we do what we do and how to change - Duhigg, Charles (Great Britain : Random House Books, 2012)
Takes you to the edge of scientific discoveries that explain why habits exist and how they can be changed. This book brings to life a whole new understanding of human nature and its potential for transformation. It shows, by harnessing this science, we can transform our businesses, our communities, and our lives.
Includes index.
Keywords: Habit; Habit breaking; Habit -- Social aspects